Financial advice and asset allocation - Zhang, A (The New Zealand Finance Colloquium, 2013)
We explore differences in portfolio composition between investors who receive financial advice and those who do not. Using proprietary data from a national investment savings scheme that contains information of 405,107 individual retirement accounts, we find that financial advice is transformative. People who receive advice hold their assets differently compared to people who do not. We report five key findings. (1) Older, wealthier and female investors are more likely to receive financial advice. (2) Advised investors hold more equity assets. (3) Demographic characteristics affect asset allocation. (4) Advisers tend to recommend asset allocations in line with life-cycle based theories. (5) Investors who received advice tend to earn higher returns in years when equity markets perform well.
Keywords: Financial advice; Portfolio choice; Household finance